The role of networks in diffusion and uptake of climate-smart technologies in Rakai, Uganda: Report of project initiation workshops, 5-9 May 2014 - Ogwal-Omara, Richard; Halewood, Michael; Otieno, G.; Bioversity International (2014)
This report summarizes the first steps of a project to analyze the role of networks in the diffusion and uptake of climate-smart technologies in Rakai, Uganda. The activity is part of the Policy Action for Climate Change Adaptation (PACCA) project funded by Climate Change for Agriculture and Food Security (CCAFS). We held two workshops. The first was a participatory assessment with farmers in Rakai to understand their perceptions of climate change and resilience of their landscapes, using “indicators of resilience in socio-ecological production landscapes (SEPLs)”. The second was a workshop to develop the project work plan and tools, including a forthcoming smallholder farmers survey on networks, technologies and practices to better understand how farmers in Rakai communicate and exchange knowledge about farming practices.